Job Durations and the Job Search Model: A Two-Country, Multi-Sample Analysis - Jesper Bagger; Morten Henningsen (Statistics Norway, Research Department, 2008)
This paper assesses whether a parsimonious partial equilibrium job search model with on-the-job search can reproduce observed job durations and transitions to other jobs and to nonemployment. We allow for unobserved heterogeneity across individuals in key structural parameters. Observed heterogeneity and life cycle effects are accounted for by estimating separate models for flow samples of labor market entrants and stock samples of "mature" workers with 10-11 years of experience, by stratifying on education length and by allowing for non-search related wage growth due to accumulation of labor market experience. We use comparable register based panel data for two countries, Denmark and Norway. All workers are followed for 6 years. The model fits observed job-to-job and job-to-nonemployment hazard functions well for most samples with a better fit for entrants than for mature workers, especially for the job-to-job hazard function. We find important differences in structural parameters between entrants and mature workers and we find that the Norwegian labor market is more frictional than the Danish labor market.
Keywords: J31; J63; 330; Job Mobility; Job Durations